Measurements of the structure and circulation of the stratosphere and mesosphere, 1971-2 - Smith, Walter S.; United States. National Aeronautics and Space Administration.; Goddard Space Flight Center. (Washington : National Aeronautics and Space Administration, 1974)
METEOROLOGICAL PARAMETERS; ROCKET SOUNDING; STRATOSPHERE; ATMOSPHERIC CIRCULATION; MESOSPHERE; WIND PROFILES; ROCKET MEASUREMENTS OF STRATOSPHERE AND MESOSPHERE; TEMPERATURE, PRESSURE DENSITY AND WIND PROFILES IN THE UPPER ATMOSPHERE; METEOROLOGICAL ROCKET OBSERVATIONS "Complete data from a total of 43 meteorological rocket soundings of the stratosphere and mesosphere conducted from Barrow, Alaska; Churchill, Canada; Wallops Island Va.; and Kourou, French Guiana are presented. These data consist of temperature, pressure, density, and wind profiles from 35 acoustic grenade soundings that cover the 30 to 90 km altitude range, and temperature, pressure, and density profiles from 8 pitot probe soundings that cover the 25 to 120 km altitude range. Errors for each of the 35 acoustic grenade soundings are also included."--NTIS abstract. Chiefly tables. Cover title. Includes bibliographical references (p. 93). METEOROLOGICAL PARAMETERS; ROCKET SOUNDING; STRATOSPHERE; ATMOSPHERIC CIRCULATION; MESOSPHERE; WIND PROFILES; ROCKET MEASUREMENTS OF STRATOSPHERE AND MESOSPHERE; TEMPERATURE, PRESSURE DENSITY AND WIND PROFILES IN THE UPPER ATMOSPHERE; METEOROLOGICAL ROCKET OBSERVATIONS "Complete data from a total of 43 meteorological rocket soundings of the stratosphere and mesosphere conducted from Barrow, Alaska; Churchill, Canada; Wallops Island Va.; and Kourou, French Guiana are presented. These data consist of temperature, pressure, density, and wind profiles from 35 acoustic grenade soundings that cover the 30 to 90 km altitude range, and temperature, pressure, and density profiles from 8 pitot probe soundings that cover the 25 to 120 km altitude range. Errors for each of the 35 acoustic grenade soundings are also included."--NTIS abstract. Mode of access: Internet.